Representasi Peran dan Relasi Gender dalam Kumpulan Bahan Bacaan Literasi Jenjang SMP - Nina Alia Ariefa; Bembi Mulia Ramadhani (Universitas Al Azhar Indonesia, 2023)
In recent years, the Indonesian Ministry of Education and Culture has provided a series of reading materials for young readers with segmentation ranging from PAUD to SMA. This procurement is special because this reading material is disseminated on a national scale to improve the literacy skills of the younger generation within the framework of the National Literacy Movement (GLN). This research aims to describe gender roles and relations in this collection of reading materials. This research data is a collection of junior high school level literacy reading materials published in 2016. The data was analyzed using content analysis methods through the stages of categorization, tabulation, interpretation and inference using a feminist literary criticism approach. The results of this research show that the collection of literacy reading materials at junior high school level shows alignment with patriarchal ideology. There is a reproduction of traditional gender roles, which presents a framework of women's domestication, and a depiction of men's roles attached to the public sector. Apart from that, it seems that the depiction of agency polarization is dominant in male characters compared to female characters. The depiction of gender relations in this collection of reading materials generally shows a hierarchical form of relationship, which emphasizes the superiority of male characters. Thus, this collection of reading materials shows that there is no balance that leads to gender equality. This is important to do because this reading material becomes intake for teenagers in forming teenagers' attitudes and perceptions about gender behavior.Keywords - Feminist Literary Criticism, Gender role, Gender Relation, Literacy